Difference analogue of the Lemma on the Logarithmic Derivative with applications to difference equations - Halburd, R.G.; Korhonen, R.J. (Journal of mathematical analysis and applications, 2006)
The Lemma on the Logarithmic Derivative of a meromorphic function has many applications in the study of meromorphic functions and ordinary differential equations. In this paper, a difference analogue of the Logarithmic Derivative Lemma is presented and then applied to prove a number of results on meromorphic solutions of complex difference equations. These results include a difference analogue of the Clunie lemma, as well as other results on the value distribution of solutions.